Various amide derivatives induced Keggin-type SiW12O404−-based cobalt complexes: assembly, structure, electrochemical sensing and dye adsorption properties. Issue 6 (20th January 2022) - Li, Lei; Zhang, Yue; Wang, Xiang; Xu, Na; Li, Xiao-Hui; Wang, Xiu-Li
Abstract : Three new [SiW12 O40 ] 4− -based complexes assembled from three amide derivative ligands displayed excellent electrochemical sensing activities for BrO3 −, NO2 − and Cr(vi ) ions and showed good adsorption capacities for methylene blue and neutral red dyes. Abstract : The self-assembly of different amide derivative ligands, N -(quinoline-5-yl)-1 H- imidazole-4-carboxamide (L 1 ), 4-[(1 H- imidazole-4-carboxamide)ethyl]phenyl-1 H- imidazole-4-carboxamide (L 2 ) and bis[4-(1 H- imidazole-4-carboxamide)phenyl]methanone (L 3 ), with cobalt ions and [SiW12 O40 ] 4− anion under mixed solvent conditions presented three new Keggin-type polyoxometalate-based metal–organic complexes (MOCs), [Co(HL 1 )2 (H2 O)2 ][SiW12 O40 ] (1 ), [Co2 (L 2 )2 (H2 O)2 (SiW12 O40 )] (2 ) and [Co2 (L 3 )2 (H2 O)2 (SiW12 O40 )] (3 ), respectively. MOCs 1–3 displayed novel various two-dimensional supramolecular structures. Complex 1 consists of a mononuclear fragment {Co(L 1 )2 } and a [SiW12 O40 ] 4− anion. Complexes 2 and 3 contain a type of ladder-like chain, which was constructed from a {Co2 L2 (H2 O)2 } 4+ chain as the side rail and [SiW12 O40 ] 4− anion as the middle rail. The effects of mixed solvent ratio on the formation of MOCs and that of organic ligands on the architectures and properties were discussed. Complexes 1 and 3 not only possess electrocatalytic reduction activity for bromate, nitrite, and Cr(vi ) ions, but also show excellent electrochemical sensing behavior for bromate, nitrite, and Cr(vi ) ions. In addition, organic dyes such as methylene blue and neutral red could be effectively adsorbed by complexes 1–3 .